Pelaku Ekonomi Mikro dalam Menciptakan Kekuatan Ekonomi Nasional - Pohan, Hafni; Ruslan, Dede (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2024)
The purpose of this study is to determine the types of protection provided by the government to microeconomic actors in Mandailing Natal Regency, namely farmers, fishermen, and street vendors, and the reinsurance they receive. This study uses a quantitative descriptive approach, which measures quantitative data and objective statistics through scientific calculations from a sample of survey respondents to determine the frequency and percentage of their responses. The results show that microeconomic actors face significant challenges, such as low incomes (farmers IDR 2.8 million/6 months, fishermen IDR 1.05 million/week, traders IDR 800,000/month) and minimal guidance and protection from the government. The study's conclusions underscore the urgency of more inclusive policies to empower microeconomic actors through guidance, protection, and access to capital, in order to strengthen the national economy. These findings enrich the literature on microeconomics by emphasizing the integration of Islamic and conventional approaches in economic development. Keywords: Microeconomics, Population, Protection.